PERBANDINGAN METODE PENELITIAN HUKUM NORMATIF DAN EMPIRIS DALAM KAJIAN ILMU HUKUM - Andri Sutikno; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study compares normative and empirical legal research methods and formulates grounds for their selection and integration. It uses a structured literature review of journal articles published in 2020–2026, methodology books, and legislation. Comparative synthesis covers ontology, objectives, objects, data, approaches, collection techniques, analysis, validity, ethics, outputs, and limitations. Normative research examines law as norms through statutes, principles, concepts, cases, and doctrine, whereas empirical research examines law as behaviour, institutions, and social experience through field data. The difference does not create a methodological hierarchy. Appropriateness depends on alignment between the research question, the claim, and the evidence. Normative inquiry addresses what ought to be, how provisions should be interpreted, and whether norms are coherent; empirical inquiry examines how law is implemented, experienced, obeyed, and produces consequences. Integration is required when evaluating the gap between law in books and law in action. The proposed model proceeds from mapping normative mandates, operationalising indicators, collecting empirical evidence, comparing findings, and formulating recommendations. It strengthens validity and prevents the use of methodological labels without clear design consequences.